The Effect of Internal Communication, Teamwork, and Employee Empowerment on Employee Performance at the Medan City Social Service Office - Tambunan, Nia Mendawati; Sinurat, Siti Normi; Sinurat, Elperida (Jurnal Bisnis Mahasiswa, 2025)
Employee performance is a key factor in improving the effectiveness of public services, which can be influenced by various managerial aspects in the organization. Effective internal communication is expected to enhance understanding and coordination of work among employees, while teamwork fosters synergy within the work environment. Employee empowerment plays a crucial role in improving employee motivation and productivity. Based on the results of simultaneous hypothesis tests, it can be concluded that internal communication, teamwork, and employee empowerment simultaneously have a significant influence on employee performance. Based on the analysis of the determination coefficient, the value of the determination coefficient or Adjusted R-Square is 0.574 or 57%, which means that the influence of internal communication, teamwork, and employee empowerment on employee performance is 57%. In comparison, the remaining 43% (100%-57 %) is influenced by other variables or factors that are not studied.